Karakteristik dan Ciri-ciri Fundamentalisme sebagai Aliran dan Gerakan Keagamaan - Tridarmanto, Yusak; Soetapa, Djaka (Unisia, 2016)
The two writers of the article below describe the characteristics of fundamentalism as a school and a movement of religion. Some of them are as a moral movement to return to fundamental truth In the uncertainty of society life, back to the tenet of Holy Scripture that never denies as a guidance of daily life. In this sense, it has similarities to orthodoxy but the differences how to apply the truth of Holy Book in society. The fundamentalism believes the coming of the Thousand Year Kingdom. It does not hesitate to confront and isolate the sinning people who are not in accordance with belief norms, the fundamentalists believe that they are guided saved people, while the people are not in their group go astray. The fundamental ism movement in the beginning is sporadic individual not organize, it involves in the political domain. The writers declare that the elements of fundamentalism that mentioned above there are in every group of fundamentalism, the particular elements exist in one group whereas the other elements emerge in the other group. At least, the essence of the fundamentalism movement as effort to refer the pure doctrine to protect many kinds of fundamentalism.